Hubungan Dukungan Sosial Dengan Beban Kerja Perawat Di Ruang Rawat Inap Rumah Sakit Murni Teguh Sudirman Jakarta - Tampubolon, Yunita Nomianse; Tambunan, Dior Manta (Universitas Murni Teguh, 2025)
xcessive workload greatly affects the productivity of health workers and will affect theproductivity of nurses. The objective of this study is to determine the relationship betweensocial support and the workload of inpatient nurses at Murni Teguh Sudirman Hospital,Jakarta. Research method is quantitative type with cross sectional design. The number ofsamples in this study was 30 respondents using total sampling. The results of the Pearsonanalysis test obtained a significance value or sig (2-tailed), namely 0.000. Because the sig(2-tailed) value is 0.000 < 0.05, it can be said that there is a significant relationship betweensocial support and workload. It is concluded that there is a relationship between socialsupport and the workload of nurses in the inpatient room at Murni Teguh Sudirman Hospital,Jakarta. It is suggested for future researchers to increase the number of research samplesand add variables such as work experience and the quality of nursing services.